Critical Discourse Analysis Innovation of Sekolah Rakyat for Educational Solutions in Indonesia - Erlina Puspitaloka Mahadewi; Ayu Larasati; Nutrient Hulu; Mohamad Reza Hilmy; Pratidina Ekanesia; Setia Nugraha; Arman Arman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The gap in access to education in Indonesia remains a serious problem, especially for low-income or poor families. To address this issue, the government launched Sekolah Rakyat Program, as a strategy for educational equality that emphasizes inclusiveness and social justice. This study analyzes the discourse on Sekolah Rakyat Menengah Pertama 9, Bandung Indonesia policy using Norman Fairclough's Critical Discourse Analysis (CDA), which encompasses three dimensions: text analysis, discursive practice, and social practice. Data was obtained through a documentary study of policy documents, online media coverage, and statements from school and government officials. The results show that in the text dimension, the use of diction such as free and digital-based education builds the image of a friendly and inclusive nation. In the discursive practice dimension, discourse is produced and disseminated by the government through the media to strengthen the positive political legitimacy of its results. In the social practice dimension, this program presents itself as a response to inequality and disparities in education while simultaneously creating a new social practice in the form of inclusive and dignified digital education in Indonesia. Critically, this study concludes that Sekolah Rakyat Program is not only an education policy, but also an instrument of ideological legitimacy and political hegemony, that shapes the narrative of a positive direction for educational equality in Indonesia.